KEEFEKTIFAN INKUIRI TERBIMBING BERORIENTASI GREEN CHEMISTRY TERHADAP KETERAMPILAN PROSES SAINS - Afiyanti, Nur Amalia; Cahyono, Edy; -, Soeprodjo (Jurnal Inovasi Pendidikan Kimia, 2014)
This research aims to know the effectiveness of guided inquiry oriented green chemistry for science process skills at XI school grade of SMA in Semarang on 2012/2013 period. The population is normal and homogeneous, so to take two groups of samples using cluster random sampling techniques. Design of this research is posttest only control design. The succes of this research seen from cognitive aspect of student achievement reach KKM. At the final stage of the analysis, the t test used was left-test with t count > t table (1.696). The student achievement for experimental classes obtained t count of 3.860 while the control class 0,914. This suggests that the experimental class has achieved mastery learning, while the control class not yet. The average value of the psychomotor aspects of students in the experimental class was 82.6 which is included in the excellent category and control class was 74 included in good category. In the aspect of Students environmental concern, the average value of the experimental class was 88.65 included in the excellent category and class control was 81.7 included in good category. The conclusion was that the research-oriented guided inquiry of green chemistry proved effectively increase the science process skills.Keywords: Green Chemistry, Guided Inquiry, Science Process Skills